The CroCo cross-link converter: a user-centred tool to convert results from cross-linking mass spectrometry experiments - Bender, Julian (Bioinformatics, 2020)
MOTIVATION: A variety of search engines exists for the identification of peptide spectrum matches after cross-linking mass spectrometry experiments. The resulting diversity in output formats complicates data validation and visualization as well as exchange with collaborators, particularly from other research areas. RESULTS: Here, we present CroCo, a user-friendly standalone executable to convert cross-linking results to a comprehensive spreadsheet format. Using this format, CroCo can be employed to generate input files for a selection of the commonly utilized validation and visualization tools. AVAILABILITY AND IMPLEMENTATION: The source-code is freely available under a GNU general public license at https://github.com/cschmidtlab/croco. The standalone executable is available and documented at https://cschmidtlab.github.io/CroCo. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.